Cakrawala Social Science: Philosophical Perspectives on Social Complexity - Fitri Sania; Ris'an Rusli (Aqlania, 2025)
This article discusses the philosophical relationship and horizon of social science as an integrative effort between the thoughts of philosophers and the scope of the development of social science as a structured discipline. Social science covers issues concerning society, individuals, social interactions, and institutions that shape human life. In this context, philosophical aspects provide essential ontological, epistemological, and axiological foundations in the development of social theories. This research uses a qualitative-descriptive approach with a library research method, through content analysis of various relevant literature. The purpose of this study is to explain the importance of integration between the philosophical dimension and the horizon of social science in understanding social phenomena more comprehensively. The results of the study show that the relationship between philosophy and social science involves various approaches and paradigms that enrich the perspective on social reality. Theories from structuralism to social action show the dynamics between social structures and individual behaviour. In addition, the horizons of social science are closely linked to other disciplines such as economics, politics and psychology, making them relevant in addressing contemporary challenges. The findings confirm that philosophical approaches in social science are not only conceptual, but also provide practical contributions in formulating social policies that are more humane and inclusive.